A Computational Method for Two-Point Boundary Value Problems of Fourth-Order Mixed Integrodifferential Equations. (22nd April 2013) - Al-Smadi, Mohammed; Abu Arqub, Omar; Momani, Shaher
Abstract : In this paper, reproducing kernel Hilbert space method is applied to approximate the solution of two-point boundary value problems for fourth-order Fredholm-Volterra integrodifferential equations. The analytical solution was calculated in the form of convergent series in the space W 2 5 [ a, b ] with easily computable components. In the proposed method, the n -term approximation is obtained and is proved to converge to the analytical solution. Meanwhile, the error of the approximate solution is monotone decreasing in the sense of the norm of W 2 5 [ a, b ] . The proposed technique is applied to several examples to illustrate the accuracy, efficiency, and applicability of the method.